2016
DOI: 10.1007/s00405-016-4031-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of misoprostol against cisplatin-induced ototoxicity

Abstract: Cis-diammineedichloroplatinum (cisplatin) is a chemotherapeutic agent that is widely used in the treatment of many cancers. Nephrotoxicity, ototoxicity and neurotoxicity are dose-limiting adverse effects for cisplatin. The cellular and molecular mechanisms underlying cisplatin-induced ototoxicity aren't fully understood. It has been proposed that cisplatin primarily cause damage at the cochlea, outer hair cells in particular, leading to excessive production of free oxygen radicals in the organ of Corti, stria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It has been stated that MS has a protective effect against mucosal lesions in the stomach and liver damage patients with hepatitis B 12 . In mice a lipopolysaccharide induced endotoxicity model, MS had positive effects on brain antioxidant parameters and decreased serum AST and ALT levels 13 , and in rats it has been reported to have a protective effect against acetaminophen-induced liver damage and cisplatin-induced ototoxicity, same animals it has a protective effect against acetaminophen-induced microvascular liver damage, and a positive effect against CCl 4 -induced liver damage [14][15][16][17] . Some researchers have been reported that, prostaglandins (PGs) (as to be cytoprotective) are triggering the liver regeneration cascade by using proliferative factor (include hepatocyte growth factor (HGF), epidermal growth factor (EGF), and interleukin-6 (IL-6)) after PH in rats 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that MS has a protective effect against mucosal lesions in the stomach and liver damage patients with hepatitis B 12 . In mice a lipopolysaccharide induced endotoxicity model, MS had positive effects on brain antioxidant parameters and decreased serum AST and ALT levels 13 , and in rats it has been reported to have a protective effect against acetaminophen-induced liver damage and cisplatin-induced ototoxicity, same animals it has a protective effect against acetaminophen-induced microvascular liver damage, and a positive effect against CCl 4 -induced liver damage [14][15][16][17] . Some researchers have been reported that, prostaglandins (PGs) (as to be cytoprotective) are triggering the liver regeneration cascade by using proliferative factor (include hepatocyte growth factor (HGF), epidermal growth factor (EGF), and interleukin-6 (IL-6)) after PH in rats 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our study is the first to provide preliminary evidence that inherited GSTT1 and GSTP1 Ile105Val polymorphisms can alter gastrointestinal status, nephrotoxicity, ototoxicity, pharmacokinetics, and survival in HNSCC patients treated with CDDP chemoradiation. In this context, GST genotypes can be used as instruments for assessing toxicity of CDDP-based therapies by selecting HNSCC patients for the use of specific anti-emetics and protective renal and auditory system agents, thereby saving patients from the side effects of chemotherapy 14,35,36 and reducing treatment costs 37 . However, we are aware that the number of patients enrolled in study was not large, and that further larger studies and functional analyses of relevant polymorphisms are required to confirm the roles of these GST s in disease.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that further analysis in a larger number of patients and functional analyses of relevant SNPs will be required to confirm results and elucidate their roles in disease. We believe that these results may contribute to the future personalized treatment of HNSCC patients, possibly with the use of varying CDDP doses and protective agents against CDDP-induced nephro- and ototoxicity [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%